Next-Day Solar Irradiance Forecasting: A Preliminary Study in Limassol - Fragkos, Konstantinos; Charalampous, Georgia; Fountoulakis, Ilias; Papachristopoulou, Kyriakoula; Hadjimitsis, Diofantos G.; Kazadzis, Stelios (My University, 2024)
This study presents a preliminary evaluation of a next-day solar irradiance forecast system in Limassol, Cyprus, over six months. For the evaluation, forecasted Global Horizontal Irradiance (GHI) was compared with high-quality ground measurements. The system showed strong correlation with measured values at both hourly and daily timescales. Hourly forecasts exhibited a correlation coefficient (r2) of 0.84 and a Mean Bias Error (MBE) of 23.4 W/m2 (4.8%), while daily energy forecasts showed improved performance with an r2 of 0.86 and an MBE of 0.3 kWh/m2 (4.7%). The Root Mean Squared Error (RMSE) was 123.7 W/m2 (25.4%) for hourly forecasts and 0.8 kWh/m2 (13%) for daily forecasts, indicating that daily aggregation reduces error magnitudes by averaging out short-term fluctuations and discrepancies. Some discrepancies were due to the model’s limited ability to capture cloud and aerosol variations. Future work will focus on investigating these factors to enhance the forecast system’s accuracy and reliability.
Keywords: Solar Irradiance Forecasting; Next-Day Energy Forecast; Cloud Modification Factor; Aerosol Load